2009
DOI: 10.1002/adma.200900086
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Controlled Catalytic Nanowire Growth from Solution

Abstract: Electric‐field‐induced catalytic growth of cadmium selenide nanowires from solution is demonstrated. Our approach highlights the importance of electric field and surface‐charge density for catalytic nanowire growth. In addition, this method is compatible with conventional silicon‐based technology, and we demonstrate in situ device fabrication at temperatures below 300 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…This behavior could be related to the zinc-blende crystal structure of InP and the twinning behavior observed in MOCVD grown InP nanowires by Woo et al 29 In contrast, CdSe nanowires grown by the EC-SLS technique show a high degree of crystallinity owing to their preferred growth direction along the (001) axis of the wurtzite crystal lattice. 13 We attribute the approximately 5 nm thick amorphous Figure 3d. The higher average atomic percentage of indium, 56%, relative to phosphorus, 44%, can be attributed to the indium-rich native oxide layer typically observed on InP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior could be related to the zinc-blende crystal structure of InP and the twinning behavior observed in MOCVD grown InP nanowires by Woo et al 29 In contrast, CdSe nanowires grown by the EC-SLS technique show a high degree of crystallinity owing to their preferred growth direction along the (001) axis of the wurtzite crystal lattice. 13 We attribute the approximately 5 nm thick amorphous Figure 3d. The higher average atomic percentage of indium, 56%, relative to phosphorus, 44%, can be attributed to the indium-rich native oxide layer typically observed on InP.…”
Section: Resultsmentioning
confidence: 99%
“…13 The EC-SLS method enables the simultaneous synthesis and integration of nanowires into device geometries. In this article, we extend the EC-SLS technique to the growth of InP nanowires.…”
mentioning
confidence: 99%
“…[49] For preparing an Au-Si eutectic compound, a temperature higher than the boiling point of the solvent is required. In a recent paper, the electrically controlled solution-liquid-solid (EC-SLS) method was designed by Dorn et al [51] By using this method, they reported the synthesis of CdSe and InP nanowires that were controllably grown between two electrodes. After the formation of Au-Si alloy, the further growth processes seemed very analogous to those in the case of the VLS or SLS method.…”
Section: The Solution-liquid-solid (Sls) Synthetic Methods For Semiconmentioning
confidence: 99%
“…Therefore, nanowires were synthesized in the supercritical solution phase. [51,52] This method facilitates the direct integration of solution processed nanowires into devices. From this result, they proposed the supercritical-fluid-liquid-solid (SFLS) synthetic method.…”
Section: The Solution-liquid-solid (Sls) Synthetic Methods For Semiconmentioning
confidence: 99%
“…The most promising and now extensively used method for achieving novel structures is solution process [1][2][3][4][5][6]. Recently, many efforts have been focused on the organization of low-dimensional building blocks into two-and three-dimensional (2D and 3D) hierarchical structures.…”
Section: Introductionmentioning
confidence: 99%